CLINICAL EVALUATION OF SHOBHANJANA (SHIGRU) ROOT BARK IN THE MANAGEMENT OF MUTRASHMARI (UROLITHIASIS) - Babu, *P.V.Mahesh; Shivudu, K.V.; Maheswar, T.; Saiprasad, A.J.V. (International Journal of Ayurveda and Pharma Research, 2016)
A clinical study was conducted to evaluate the efficacy of Shobhanjana (Moringa Olifera) root bark in the management of Mutrashmari (Urolithiasis) at OPD/IPD of S.V.Ayurvedic Hospital, Tirupati. Total number of 30 cases enrolled for the study. The drug Shobhanjana root bark Kwatha (decoction) was given in the dose of 24 ml twice daily before food for one month period. Follow up was carried out at weekly intervals. The effect of treatment was observed highly significant in relieving pain, dysuria, haematuria and also found statistically significant improvement in removing the renal calculus. The study was also planned to find out the effect of the drug on different types of Ashmari (Vata, Pitta, Kapha and Sukraja) and results of the study have shown that the drug is more effective in the management of Kapha & Vataja types of Ashmari. Maximum result was observed in renal calculi in comparison to the calculi present in Ureter and Urinary bladder. On the basis of overall assessment the drug Shobhanjana root bark on Mutrashmari has shown complete relief in 16 (53.3%) cases, Marked improvement in 12 (40%) cases and No improvement in 2 (6.6%) cases.